2020
DOI: 10.3390/cancers12082268
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin E2 Promotes Whole Genome Doubling in Breast Cancer

Abstract: Genome doubling is an underlying cause of cancer cell aneuploidy and genomic instability, but few drivers have been identified for this process. Due to their physiological roles in the genome reduplication of normal cells, we hypothesised that the oncogenes cyclins E1 and E2 may be drivers of genome doubling in cancer. We show that both cyclin E1 (CCNE1) and cyclin E2 (CCNE2) mRNA are significantly associated with high genome ploidy in breast cancers. By live cell imaging and flow cytometry, we show that cycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…As a downstream transcriptional target, CCNE2 was also involved in cell cycle and cell proliferation. CCNE2 was a member of Cyclin E family and CCNE2 with the other Cyclin E family members functioned alike, which activated the CDK2 to promote cell cycle progression (Geng et al, 1996;Lee et al, 2020). In our results, we found that in TGF-β1-stimulated HCFs, the cell proliferation ability was enhanced and the cell cycle was promoted by improving percentages of the S and G2/M phase.…”
Section: Discussionsupporting
confidence: 56%
“…As a downstream transcriptional target, CCNE2 was also involved in cell cycle and cell proliferation. CCNE2 was a member of Cyclin E family and CCNE2 with the other Cyclin E family members functioned alike, which activated the CDK2 to promote cell cycle progression (Geng et al, 1996;Lee et al, 2020). In our results, we found that in TGF-β1-stimulated HCFs, the cell proliferation ability was enhanced and the cell cycle was promoted by improving percentages of the S and G2/M phase.…”
Section: Discussionsupporting
confidence: 56%
“…Importantly, the effects of high levels of Cyclin E1 on chromosome instability seem to depend on CDK2 activity, as a hyperactive CDK2 knockin allele was sufficient to induce increased Cyclin E1-associated CDK2 activity and micronucleus formation in human colorectal cancer cells ( Hughes et al, 2013 ). CCNE1 and CCNE2 amplification, as well as increased mRNA expression, have been also correlated with whole genome doublings in human cancers ( Zack et al, 2013 ; Lee et al, 2020 ). One of the proposed mechanisms to explain how hyperactive Cyclin E/CDK2 causes genome doublings is the induction of mitotic failure or endoreduplication, with subsequent formation of polyploid cells.…”
Section: Cyclin E/cdk2-induced Replication Stress Causes Genomic Instability In Human Cancersmentioning
confidence: 99%
“…This can lead to genomic instability and drive the dysregulation of genes responsible for proliferation and cellular survival [22,27]. Cyclin E1 amplification occurs in 19.1% of all ovarian cancers [22,25] and 3.4% of breast cancers [28]. Most HRD cancer cells have direct deficiency in a gene or group of genes responsible for homologous recombination DNA repair, although upregulation of miRNAs can also cause HRD [21].…”
Section: Homologous Recombination Dna Repair Proficiency (Hrp) and Cancermentioning
confidence: 99%